Wild man from Borneo : a cultural history of the orangutan - Cribb, R. B.; Gilbert, Helen, 1956-; Tiffin, Helen (University of Hawaiʻi Press, 2014)
Offers the first comprehensive history of the human-orangutan encounter. Arguably the most humanlike of all the great apes, particularly in intelligence and behavior, the orangutan has been cherished, used, and abused ever since it was first brought to the attention of Europeans in the seventeenth century. The red ape has engaged the interest of scientists, philosophers, artists, and the public at large in a bewildering array of guises that have by no means been exclusively zoological or ecological. One reason for such a long-term engagement with a being found only on the islands of Borneo and Sumatra is that, like its fellow great apes, the orangutan stands on that most uncomfortable dividing line between human and animal, existing, for us, on what has been called the dangerous edge of the garden of nature. Beginning with the scientific discovery of the red ape more than three hundred years ago, this work goes on to examine the ways in which its human attributes have been both recognized and denied in science, philosophy, travel literature, popular science, literature, theatre, museums, and film. The authors offer a provocative analysis of the origin of the name orangutan, trace how the ape has been recruited to arguments on topics as diverse as slavery and rape, and outline the history of attempts to save the animal from extinction. Today, while human populations increase exponentially, that of the orangutan is in dangerous decline. The remaining wild men of Borneo are under increasing threat from mining interests, logging, human population expansion, and the widespread destruction of forests. The authors hope that this history will, by adding to our knowledge of this fascinating being, assist in some small way in their preservation.